Carbon dioxide reduction by photosynthesis undetectable even during phytoplankton blooms in two lakes - Karla Münzner; Silke Langenheder; Gesa A. Weyhenmeyer; Bianka Csitári; Eva S. Lindström (Scientific Reports, 2023)
Abstract Lakes located in the boreal region are generally supersaturated with carbon dioxide (CO2), which emerges from inflowing inorganic carbon from the surrounding watershed and from mineralization of allochthonous organic carbon. While these CO2 sources gained a lot of attention, processes that reduce the amount of CO2 have been less studied. We therefore examined the CO2 reduction capacity during times of phytoplankton blooms. We investigated partial pressure of CO2 (pCO2) in two lakes at times of blooms dominated by the cyanobacterium Gloeotrichia echinulata (Erken, Sweden) or by the nuisance alga Gonyostomum semen (Erssjön, Sweden) during two years. Our results showed that pCO2 and phytoplankton densities remained unrelated in the two lakes even during blooms. We suggest that physical factors, such as wind-induced water column mixing and import of inorganic carbon via inflowing waters suppressed the phytoplankton signal on pCO2. These results advance our understanding of carbon cycling in lakes and highlight the importance of detailed lake studies for more precise estimates of local, regional and global carbon budgets.